Aerobic Oxidation of Imidazolines to 2-Arylimidazoles Using CuSO4∙H2O as a Catalyst; Synthesis; Vol. 57, iss. 23 - Myachina K. A. Kristina Alekseevna; Semenov A. V. Artem Valerjevich; Shurikov M. K. Matvey Konstantinovich; Dar’in D. V. Dmitry; Baykov S. V. Sergey Valentinovich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Soldatova N. S. Nataliya Sergeevna; Postnikov P. S. Pavel Sergeevich (2025, 2025)
Title screen